Providing Legal Protection for Consumers Against Standard Clauses/One-sided Agreements Made by Business Actors - Perdana, Surya; Koto, Ismail (Universitas Muhammadiyah Sumatera Utara, 2024)
Standard clauses are usually made by parties in a stronger position, which in reality can be held by business actors. The contents of standard clauses often harm the party receiving the standard clause, namely the consumer, because they are made unilaterally. If consumers reject the standard clause, they will not get the goods or services they need, because they will find similar standard clauses elsewhere. Article 1 number 1 UUPK states that,